2013
DOI: 10.1016/j.ccl.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the Mitral Valve Apparatus

Abstract: The mitral valve apparatus is a complex three–dimensional functional unit that is critical to unidirectional heart pump function. This review details the normal anatomy, histology and function of the main mitral valve apparatus components 1) mitral annulus, 2) mitral valve leaflets, 3) chordae tendineae and 4) papillary muscles. 2 and 3 dimensional Echocardiography is ideally suited to examine the mitral valve apparatus and has provided insights into the mechanism of mitral valve disease. An overview of standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(46 citation statements)
references
References 118 publications
1
45
0
Order By: Relevance
“…3D-TEE has been used extensively for MA assessment 13,[16][17][18][19][20][21][22] ; however, its utility in assessing the proposed D-shaped MA, Figure 4. A, Medial and lateral trigones are identified using both short-and long axis planes.…”
Section: Discussionmentioning
confidence: 99%
“…3D-TEE has been used extensively for MA assessment 13,[16][17][18][19][20][21][22] ; however, its utility in assessing the proposed D-shaped MA, Figure 4. A, Medial and lateral trigones are identified using both short-and long axis planes.…”
Section: Discussionmentioning
confidence: 99%
“…17 Diagnostic specificity is required to study the genetic mutations associated with this MVP. Older studies lacked this specificity and suggested that MVP prevalence was as high as 10–15% or more, 85 often on the basis of 2D views that seemed to show prolapse because of the normal saddle shape of the valve, without actual pathological leaflet displacement.…”
Section: Mitral Valve Prolapsementioning
confidence: 99%
“…64,184 Furthermore, isolated anterior and inward displacement of the papillary muscles combined with leaflet elongation, especially of the posterior leaflet, can lead to SAM, the degree of which is related to leaflet length, even in the absence of septal hypertrophy. 15,17,185192 …”
Section: Mitral Valve In Hcmmentioning
confidence: 99%
See 2 more Smart Citations